SIKAP MOTIVASI DAN PENGEMBANGAN JIWA KEWIRAUSAHAAN STUDI KASUS MAHASISWA POLITEKNIK KRIDATAMA - Evi Selvi; Dewi Untari (Widya Cipta - Jurnal Sekretari dan Manajemen, 2019)
This study discusses the motivation and development of entrepreneurial spirit Kridatama Polytechnic Bandung students request an understanding of entrepreneurship as a whole. The method used in this study is qualitative data which is presented in the form of words, not in the form of numbers, from this study are students of the third semester of the Entrepreneurship Course at Kridatama Polytechnic Bandung who gathered 98 students. The results of the discussion addressed that the Kridatama Polytechnic Bandung Students did not yet have the confidence needed and the development of entrepreneurial motivation. From the interviews of Kridatama Polytechnic students, they needed a lot of entrepreneurship training, entrepreneurship seminars and Bandung Kridatama Polytechnic students who still needed a lot of information for the development of entrepreneurial spirit. The Kridatama Polytechnic that has been formed comes from the first skills that shape mental attitudes, form superior personalities who are good at initiating and can coordinate their business activities.